2011
DOI: 10.1188/11.onf.e445-e454
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Young Survivors of Extracranial Childhood Cancer: A Finnish Nationwide Survey

Abstract: This study increases the knowledge about fatigue levels of young survivors of extracranial malignancies and identifies the need for instruments specifically designed to assess fatigue in this population. The healthcare team should pay attention to the fatigue level of young survivors, particularly SF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 35 publications
2
24
3
1
Order By: Relevance
“…Reports on previous childhood cancer cohorts have also shown similar self‐reported cancer‐related fatigue in survivors compared with norms . One explanation could be that data on childhood cancer survivors are compared with data on healthy pediatric populations, in which the prevalence of fatigue is also high.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Reports on previous childhood cancer cohorts have also shown similar self‐reported cancer‐related fatigue in survivors compared with norms . One explanation could be that data on childhood cancer survivors are compared with data on healthy pediatric populations, in which the prevalence of fatigue is also high.…”
Section: Discussioncontrasting
confidence: 57%
“…This instrument measures both the child's and his/her parent's perception of fatigue in pediatric patients . It has often been used in childhood cancer patients . This 18‐item questionnaire has three subscales: general fatigue (six items), sleep/rest fatigue (six items), and cognitive fatigue (six items).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All reviewed articles show that emotional functioning score among adolescents surviving cancer did not significantly differ from emotional functioning among healthy controls (Dijk et al, 2007;Eilertsen et al, 2012;Kupeli et al, 2011;Mort, Salantera, Matomaki, Salmi, Lahteenmaki, 2011;Meeske et al, 2007;Servitzoglou et al, 2007;Wu et al, 2007).…”
Section: Emotional Functioningmentioning
confidence: 99%
“…Several studies reveal that adolescents surviving cancer had good school functioning compared with healthy controls (Dijk et al, 2007;Eilertsen et al, 2012;Meeske et al, 2007;Mort et al, 2011;Wu et al, 2007) but Kupeli and his team found that adolescents surviving cancer had a significant lower score in school function compared with healthy controls (Kupeli et al, 2011).…”
Section: School/cognitive Functioningmentioning
confidence: 99%